2016
DOI: 10.1038/ejcn.2016.39
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whey protein on blood lipid profiles: a meta-analysis of randomized controlled trials

Abstract: Previous studies have suggested that whey supplementation may have beneficial effects on lipid profiles, although results were inconsistent. A literature search was performed in March 2015 for randomized controlled trials observing the effects of whey protein and its derivatives on circulating levels of triacylglycerol (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C). A meta-analysis was subsequently conducted. The meta-analysis results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 45 publications
0
23
2
Order By: Relevance
“…Accordingly, the hypolipidaemic effects of whey protein might be related to the inhibitory effects of its functional components on the absorption of cholesterol and fatty acids, increased faecal sterols excretion, and enhanced liver lipid metabolism. Zhang et al () also stated that functional components in whey such as β‐lactoglobulin proteins might have a hypocholesterolaemic effect. Since β‐lactoglobulin belongs to the lipocalin family, it is likely to decrease lipid absorption in the gut by capturing hydrophobic molecules (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the hypolipidaemic effects of whey protein might be related to the inhibitory effects of its functional components on the absorption of cholesterol and fatty acids, increased faecal sterols excretion, and enhanced liver lipid metabolism. Zhang et al () also stated that functional components in whey such as β‐lactoglobulin proteins might have a hypocholesterolaemic effect. Since β‐lactoglobulin belongs to the lipocalin family, it is likely to decrease lipid absorption in the gut by capturing hydrophobic molecules (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al () also stated that functional components in whey such as β‐lactoglobulin proteins might have a hypocholesterolaemic effect. Since β‐lactoglobulin belongs to the lipocalin family, it is likely to decrease lipid absorption in the gut by capturing hydrophobic molecules (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of triglycerides were lower in alcoholic rats (two-way ANOVA, ethanol consumption effect, F=6.92, p<0.05; Tukey's HSD post-hoc test [10]. Here we studied the effects of whey and pumpkin seed oil supplementation on rats that chronically consumed low ethanol doses ad libitum daily for 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that ingestion of different supplements can prevent liver injury induced by chronic alcohol intake. One of them is whey [10], which has been suggested as a general liver protective mix. Whey is a popular dietetic product for reducing body weight and increasing muscle mass during body building exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Meta analyses have shown no effect of whey supplementation on circulating levels of the inflammatory marker C-reactive protein (CRP) [17], and insulin sensitivity outcomes were contradictory [18]. Small, but clinically insignificant, reductions in fasting and circulating triacylglycerol levels were reported following whey supplementation in adults ≥18 years, but no changes on other blood lipids were evident [19].…”
Section: Introductionmentioning
confidence: 99%